Socialization of Basic Software and Microsoft Word Application Training for Elementary Students - Musafa Widagdo; Purwono Purwono; Marlia Hafny Afrilies; Hadi Jayusman (Peneliti Teknologi Teknik Indonesia, 2023)
The progress of software is increasing along with the rapid development of technology. Software is made to facilitate human work. The convenience of the application cannot be maximized if users do not understand how to use it properly. This is generally caused by a lack of facilities and experts in the technology field, and it impacts users' lack of knowledge and insight. To keep pace with technological developments, each individual must learn the latest technologies, and one way is to attend training. Karang Duren Village is one of the areas in Sokaraja District, Banyumas Regency, Indonesia. Awareness in the field of Education in the Karang Duren Village area is very high, but they have problems related to education costs. This prompted the lecturers and students of Harapan Bangsa University to become resource persons in providing outreach and training to grade 6 students at SD Negeri 2 Karangduren as a form of effort to help increase insight and knowledge about operating software, especially Microsoft Word, correctly. This training is beneficial for elementary school students to add understanding and knowledge about Microsoft Word software and training. The training objectives can be achieved optimally if supported by more complete software facilities for student learning media.